Fibre laser metal deposition with wire: parameters study and temperature control - Medrano Téllez, Alexis G. (2010)
This research addresses the development of a laser metal deposition process with wire feeding and melt pool temperature control. The system consists of a2 kW fibre laser, a CNC table, a wire feeder and a temperature monitoring and control system.